ANALISIS FINANSIEL BEBERAPA PRODUK INDUSTRI KAYU HILIR : Kasus Suatu Perusahaan di Propinsi Kalimantan Selatan (A Financial Analysis on Several, Secondary wood Products : A case of an enterprise in Province South Kalimantan) - Rachman Effendi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Presently, the role of forestry sector in indonesia becomes very important. In 1990/1991,forestry sector has contributed the second largest foreign exchange after oil and gas. For the last few years, a transition has taken place in the forest industries, namely from primary industries to secondary or tertiary industries which is expected to increase added value of forest products. The objective of this study is to analize. the profitability of an enterprise producing several secondary products such as moulding, dowet, jointed board, finger jointed product, and table top.The results showed that annual production of moulding, dowel, jointed board, finger jointed product, and table top were 26.880 m3, 12,000 m3, 5.760 m3, 5.760 m3, and 2,880 m3. respectively. Production costs per cubic meter of moulding, dowel, jointed board, finger jointed product, and table top were Rps 618.053,-, Rps 612.333,-, Rps 631.537,-, Rps 622.967,- and Rps 654.417,-, respectively. Payback period was relatively short (4.04 years), Net present value (NPV) showed positive value, and internal rate of return (IRR) was higher than average bank interest. However, NPV was sensitive to a decrease in production, 15 % decrease in production would cause NPV to become negative.